Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah (Studi Pada Nasabah Kredit KUR Bank Kalsel KCP Kayutangi) - Muhammad Aditya Perdana Putra Mauliansyah; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: In order to achieve stable and sustainable economic growth. In the banking world, customer satisfaction is one proof that the bank has been able to compete in providing excellent service to every customer. The sampling method used is incidental sampling, with a sampling technique based on chance, namely anyone who is in The sample of this study is KUR Credit customers at Bank Kalsel KCP Kayutangi as many as 48 people who have made a credit agreement in 2022. The data collection method used is a questionnaire. The data analysis method in this study is validity test, reliability test, classical assumption test, F test and t test. The results of this study indicate that the variables of reliability, responsiveness, assurance, empathy and physical evidence partially and simultaneously have a significant influence on KUR customer satisfaction at Bank Kalsel KCP Kayutangi.   Keywords: Reliability, Responsiveness, Assurance, Empathy, Tangibles, Satisfaction